Quality assessment of robot assisted thoracic surgical resection of non-small cell lung cancer: nodal upstaging and mediastinal recurrence - Shahin, Ghada M. (J Thorac Dis, 2021)
BACKGROUND: Robot assisted thoracic surgery (RATS) is the minimally invasive surgical technique of choice for treatment of patients with non-small cell lung cancer (NSCLC), at the Isala Hospital. The aim of this study is to compare clinical and pathological staging results and mediastinal recurrence after RATS for anatomical resections of lung cancer as surrogate markers for quality of mediastinal lymph node dissection (MLND). METHODS: This single institute retrospective study was conducted in patients who underwent RATS for NSCLC. Excluded were patients with a history of concurrent malignant disease, with other previous neoplasms, with small cell lung cancer (SCLC) and patients in whom the robotic technique was converted to thoracotomy, prior to lymph node dissection. Data were obtained from the hospital database. The difference between clinical and pathological staging was expressed as upstaging and downstaging. Computed Tomography scanning was used for follow-up, and diagnosis of mediastinal recurrence. RESULTS: From November 2011 to May 2016, 227 patients underwent RATS at Isala Hospital Zwolle, the Netherlands. Of those, 130 (mean age, 69.5±9.3 years) met the eligibility criteria. Preoperative mediastinal lymph node staging was done by endoscopic ultrasound/endobronchial ultrasound, by positron emission tomography (PET) or mediastinoscopy. In 14 patients (10.8%) unforeseen N2 disease was found, 6 patients (4.6%) were upstaged from cN0 to pN2 and 8 patients (6.2%) were upstaged from cN1 to pN2. Mediastinal recurrence was detected in 7 patients (5.4%) during a median follow-up of 54 months (range, 1.5–102 months). CONCLUSIONS: In patients with NSCLC, who underwent anatomical resection by means of RATS, an unforeseen N2 disease rate of 10.8% was demonstrated and a mediastinal recurrence rate of 5.4%. It is concluded that robotic surgery provides an accurate lymph node dissection.